Pengaruh Kapasitas Pemasaran Media Sosial Terhadap Kinerja Keuangan UMKM: Peran Dari Hubungan Konsumen - Sarah, Ira Siti; Putri, Ivon Sandya Sari; Raga, Ridha Azka; Pertiwi, Husna Putri; Farhani, Iklima (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Research aim: Determine the effect of social media marketing capacity on business performance in MSMEs, especially in West Java Design/Methode/Approach: The research was conducted using a quantitative descriptive approach by collecting primary data through questionnaires to 150 MSME players in West Java, however, only 149 questionnaires were returned in full and could be analyzed further using the SEM-PLS test Research Finding: This study found that financial performance in MSMEs in West Java is influenced by social media marketing capacity through consumer relationships as a partial mediator Theoretical contribution/Originality: The implementation of social media marketing, social media marketing communications, and product development through social media has been proven to have a positive and significant effect on consumer relations and has been proven to have a positive and significant effect on financial performance through consumer relations as a partial mediator Practitioner/Policy implication: Proper social media marketing strategy planning and effective implementation are needed to improve the performance of MSMEs, especially in the West Java area which is the focus of this study Research limitation: This research specifically only examines MSMEs in West Java